2015
DOI: 10.1161/strokeaha.114.007659
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Efficacy on Ischemic Stroke Recovery

Abstract: Therefore, we designed this randomized controlled trials with a larger sample, and scales to Background and Purpose-Acupuncture is a frequently used complementary treatment for ischemic stroke in China but the evidence available from previous randomized trials is inconclusive. The objective of this study was to assess the efficacy and safety of acupuncture in a more robustly designed larger scale trial. Methods-This is a multicenter, single-blinded, randomized controlled trial. Eight hundred sixty-two hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…As a novel combinational approach, electroacupuncture (EA) therapy, consisting of traditional acupuncture and modern electrotherapy technology, was frequently reported to alleviate cognitive decline in patients with stroke [2], Alzheimer disease (AD) [3, 4], or mild cognitive impairment (MCI) [57]. In addition, EA was suggested to prevent cognitive deficits in rats with cerebral ischemia [811].…”
Section: Introductionmentioning
confidence: 99%
“…As a novel combinational approach, electroacupuncture (EA) therapy, consisting of traditional acupuncture and modern electrotherapy technology, was frequently reported to alleviate cognitive decline in patients with stroke [2], Alzheimer disease (AD) [3, 4], or mild cognitive impairment (MCI) [57]. In addition, EA was suggested to prevent cognitive deficits in rats with cerebral ischemia [811].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most sham acupuncture used in previous studies is by inserting at different points. However, it is also a kind of acupuncture [32], and might induce underlying physiological effects [33], and therefore confuses the interpretation of the results. In view of this, we took the conventional treatment as control.…”
Section: Discussionmentioning
confidence: 99%
“…Although a Cochrane study [17] concluded that there was inadequate evidence to draw any conclusions as to the efficacy of this methodology, a meta-analysis [18] demonstrates its efficacy and safety. Few studies integrating acupuncture into post-stroke rehabilitation therapy have been performed in western countries [19,20]: to date, most have been conducted in the East, where acupuncture is a common and acknowledged therapy [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%